A Systematic Search for Candidate Supermassive Black Hole Binaries Using Periodic Mid-infrared Light Curves of Active Galactic Nuclei - Di Luo; Ning Jiang; Xin Liu (The Astrophysical Journal)
Periodic variability in active galactic nuclei (AGNs) is a promising method for studying subparsec supermassive black hole binaries (SMBHBs), which are a challenging detection target. While extensive searches have been made in the optical, X-ray, and gamma-ray bands, systematic infrared (IR) studies remain limited. Using data from the Wide-field Infrared Survey Explorer (WISE), which provides unique decade-long mid-IR light curves with a six-month cadence, we have conducted the first systematic search for SMBHB candidates based on IR periodicity. Analyzing a parent sample of 48,932 objects selected from about half a million AGNs, we have identified 28 candidate periodic AGNs with periods ranging from 1268 to 2437 days (in the observer frame), by fitting their WISE light curves with sinusoidal functions. However, our mock simulation of the parent sample indicates that stochastic variability can actually produce a similar number of periodic sources, underscoring the difficulty in robustly identifying real periodic signals with WISE light curves, given their current sampling. Notably, we find no overlap between our sample and optical periodic sources, which can be explained by a distinct preference for certain periods due to selection bias. By combining archived data from different surveys, we have identified a candidate exhibiting periodic behavior in both the optical and IR bands, a phenomenon that warrants further validation through observational tests. Our results highlight the potential of IR time-domain surveys, including future missions such as the Nancy Grace Roman Space Telescope, for identifying periodic AGNs, but complementary tests are still needed to determine their physical origins, such as SMBHBs.